Growth of Odot Grass (Pennisetum purpureum cv. Mott) on Sandy Marginal Land on Payung Island Kepulauan Seribu Jakarta - Syamsu Bahar; A. Saenab; N. Riris Sodular (Jurnal Sains dan Teknologi Peternakan, 2020)
Odot grass (Pennisetum purpureum cv. Mott) is a potential forage to be developed in order to guarantee goats feed in Payung island, Kepulauan Seribu Regency, DKI Jakarta province. The purpose of this study was to determine the effect of fertilizer treatment on growth and forage production odot grasses, namely the treatment of organic fertilizer in the form of goat urine and the treatment of commercial inorganic fertilizers, namely NPK fertilizer.This study was in the form of a field trial using a randomized block design with three treatments and six replications. The treatments were 1) Goat urine fertilizer 500 ml per clump; 2) NPK fertilizer 5 grams per clump and 3) Control (without fertilizer). Goat urine was taken from the location of the goat pen that has been stored for two months fermentation increased nutrient quality. Fertilization with goat urine organic fertilizer on odot grass gave vegetative growth and forage production responses as well as the use of NPK commercial inorganic fertilizers.